On the tidal resonance of the Bristol Channel - Gao, C; Adcock, T (International Society of Offshore and Polar Engineers, 2017)
The Bristol Channel has one of the largest tidal ranges in the world. A key cause for this is the resonance with the dominant semi-diurnal tides. In this paper we use numerical simulations to investigate this resonance. We first vary the frequency on the boundary of the model and examine at which frequency the model is excited. Secondly we apply a disturbance to the model and analyse the period at which it resonates. We examine the sensitivity of these results finding them sensitive to the bed friction used (with possible implications for energy extraction) but insensitive to small changes in the tidal amplitude on the boundary or the mean-water level.